Perlindungan Hukum terhadap Anak Korban Eksploitasi Seksual Komersial Berdasarkan Kajian Viktimologi - Bella Harviani (CV Rewang Rencang, 2025)
Commercial sexual exploitation of children is a serious and complex violation of human rights. This crime affects not only the physical but also the psychological well-being and future of the child victims. This study aims to examine the factors that cause children to become victims of commercial sexual exploitation and to analyze the legal protection provided to these victims from a victimology perspective. The research employs a normative juridical approach using literature review as the primary method, and applies victimological analysis to understand the position of victims within the legal system. The findings reveal that the causes can be categorized into internal factors (individual, family, education, economic) and external factors (environment and law enforcement). Legal protection for child victims is divided into two forms: preventive protection through education and regulation, and repressive protection through rehabilitation, legal assistance, and psychological recovery. Despite the existence of regulations, weak law enforcement and low public awareness remain major obstacles in the implementation of effective protection. Therefore, strong collaboration among all sectors is needed to ensure the fulfillment of children's rights and justice for victims of commercial sexual exploitation.